Prenatal Cadmium Exposure Alters Proliferation in Mouse CD4+ T Cells via LncRNA Snhg7 - McCall, Jamie L.; Varney, Melinda E.; Rice, Emily; Dziadowicz, Sebastian A.; Hall, Casey; Blethen, Kathryn E.; Hu, Gangqing; Barnett, John B.; Martinez, Ivan (Frontiers in Immunology, 2022)
Objective: Prenatal cadmium (Cd) exposure leads to immunotoxic phenotypes in the offspring affecting coding and non-coding genes. Recent studies have shown that long non-coding RNAs (lncRNAs) are integral to T cell regulation. Here, we investigated the role of long non-coding RNA small nucleolar RNA hostgene 7 (lncSnhg7) in T cell proliferation. Methods: RNA sequencing was used to analyze the expression of lncRNAs in splenic CD4+ T cells with and without CD3/CD28 stimulation. Next, T cells isolated from offspring exposed to control or Cd water throughout mating and gestation were analyzed with and without stimulation with anti-CD3/CD28 beads. Quantitative qPCR and western blotting were used to detect RNA and protein levels of specific genes. Overexpression of a miR-34a mimic was achieved using nucleofection. Apoptosis was measured using flow cytometry and luminescence assays. Flow cytometry was also used to measure T cell proliferation in culture. Finally, lncSnhg7 was knocked down in splenic CD4+ T cells with lentivirus to assess its effect on proliferation. Results: We identified 23 lncRNAs that were differentially expressed in stimulated versus unstimulated T cells, including lncSnhg7. LncSnhg7 and a downstream protein, GALNT7, are upregulated in T cells from offspring exposed to Cd during gestation. Overexpression of miR-34a, a regulator of lncSnhg7 and GALNT7, suppresses GALNT7 protein levels in primary T cells, but not in a mouse T lymphocyte cell line. The T cells isolated from Cd-exposed offspring exhibit increased proliferation after activation in vitro, but Treg suppression and CD4+ T cell apoptosis are not affected by prenatal Cd exposure. Knockdown on lncSnhg7 inhibits proliferation of CD4+ T cells. Conclusion: Prenatal Cd exposure alters the expression of lncRNAs during T cell activation. The induction of lncSnhg7 is enhanced in splenic T cells from Cd offspring resulting in the upregulation of GALNT7 protein and increased proliferation following activation. miR-34a overexpression decreased GALNT7 expression and knockdown of lncSnhg7 inhibited proliferation suggesting that the lncSnhg7/miR-34a/GALNT7 is an important pathway in primary CD4+ T cells. These data highlight the need to understand the consequences of environmental exposures on lncRNA functions in non-cancerous cells as well as the effects in utero.